2005
DOI: 10.1176/appi.ap.29.4.350
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Survey of Patient-Initiated Assaults on Medical Students During Clinical Clerkship

Abstract: Clinical clerks are at risk of PIA during their training. Students experiencing PIA feel that current levels of pre-clerkship training do not adequately inform them of the resources available after such an incident. These findings underline the need for PIA programs in the undergraduate curriculum including preclerkship training and clear, institution-wide reporting guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
3
4
0
Order By: Relevance
“…[18] Many studies report that healthcare staff, including students, is exposed to more violent behaviours from patients and relatives in psychiatric clinics. [14,41,[44][45][46] The current results confirm these findings, as student nurses' ranked psychiatric clinics as the least safe place for clinical practice. However, in a study investigating horizontal violence in the first professional year, McKenna et al [41] found lower rates of horizontal violence in psychiatric clinics compared to other clinics.…”
Section: Consequences Of Violencesupporting
confidence: 83%
“…[18] Many studies report that healthcare staff, including students, is exposed to more violent behaviours from patients and relatives in psychiatric clinics. [14,41,[44][45][46] The current results confirm these findings, as student nurses' ranked psychiatric clinics as the least safe place for clinical practice. However, in a study investigating horizontal violence in the first professional year, McKenna et al [41] found lower rates of horizontal violence in psychiatric clinics compared to other clinics.…”
Section: Consequences Of Violencesupporting
confidence: 83%
“…These findings from the present study are consistent with previously published findings [1][2][3][4][5][6][7][8][9][10][11][12][13] and document the presence of patient assault on staff as an ongoing occupational hazard in health care work settings. First, the present findings are consistent with previously published research [1][2][3][4][5][6][7][8][9][10][11][12][13] in establishing the characteristics of staff most at risk: mental health workers in inpatient settings, residential house counselors, and trainees, especially those in all three groupings who are younger and have less experience and less training.…”
Section: Discussionsupporting
confidence: 93%
“…First, the present findings are consistent with previously published research [1][2][3][4][5][6][7][8][9][10][11][12][13] in establishing the characteristics of staff most at risk: mental health workers in inpatient settings, residential house counselors, and trainees, especially those in all three groupings who are younger and have less experience and less training. As in previous studies [3,15], experienced nurses who were assaulted in restraint procedures were a fourth high risk group.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations